2018
DOI: 10.1523/jneurosci.1862-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic Receptor M3R Signaling Prevents Efficient Remyelination by Human and Mouse Oligodendrocyte Progenitor Cells

Abstract: Muscarinic receptor antagonists act as potent inducers of oligodendrocyte differentiation and accelerate remyelination. However, the use of muscarinic antagonists in the clinic is limited by poor understanding of the operant receptor subtype, and questions regarding possible species differences between rodents and humans. Based on high selective expression in human oligodendrocyte progenitor cells (OPCs), we hypothesized that MR is the functionally relevant receptor. Lentiviral MR knock-down in human primary C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 68 publications
0
39
0
Order By: Relevance
“…Human and rodent precursors/progenitors respond similarly to most growth factors such as platelet-derived growth factor (PDGF), neurotrophin-3 (NT3), and insulin-like growth factor 1 (IGF1) (Wilson, Onischke, & Raine, 2003), However, fibroblast growth factor 2 (FGF2) promotes specification and proliferation of mouse-derived cells (Gabay, Lowell, Rubin, & Anderson, 2003) but does not promote generation of oligodendrocytes from human-derived precursors (Chandran et al, 2004). While human and rodent OPC respond to muscarinic receptor (MR) signaling for their differentiation, human OPC express fewer MR than rodent cells, an important finding in promyelinating drug development (Welliver et al, 2018). Thus while comparable, rodent and human oligodendroglial lineages exhibit several differences in their biology.…”
Section: Transcription and Growth Factors Regulating Differentiatiomentioning
confidence: 99%
“…Human and rodent precursors/progenitors respond similarly to most growth factors such as platelet-derived growth factor (PDGF), neurotrophin-3 (NT3), and insulin-like growth factor 1 (IGF1) (Wilson, Onischke, & Raine, 2003), However, fibroblast growth factor 2 (FGF2) promotes specification and proliferation of mouse-derived cells (Gabay, Lowell, Rubin, & Anderson, 2003) but does not promote generation of oligodendrocytes from human-derived precursors (Chandran et al, 2004). While human and rodent OPC respond to muscarinic receptor (MR) signaling for their differentiation, human OPC express fewer MR than rodent cells, an important finding in promyelinating drug development (Welliver et al, 2018). Thus while comparable, rodent and human oligodendroglial lineages exhibit several differences in their biology.…”
Section: Transcription and Growth Factors Regulating Differentiatiomentioning
confidence: 99%
“…Our finding that DFP decreases maturation of oligodendrocytes is consistent with the current literature about the role of ACh signaling on oligodendrocyte development (Fields et al, ). In MS human clinical trials and MS animal models, inhibition of muscarinic receptors and consequent inhibition of ACh signaling is shown to promote remyelination (Abiraman et al, ; Green et al, ; Li et al, ; Liu et al, ; Mei et al, ; Welliver et al, ). Therefore, our finding that elevated ACh signaling decreases the number of mature oligodendrocytes is consistent with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Corticosterone treatment has been shown to inhibit OPC proliferation (Alonso, 2000), promote OPC differentiation (Mann et al, 2008), and shorten the node of Ranvier length (Miyata et al, 2016). Inhibition of ACh signaling promotes remyelination in experimental autoimmune encephalomyelitis studies, an animal model of Multiple Sclerosis (MS), and in human MS clinical trials (Abiraman et al, 2015;Green et al, 2017;Li, He, Fan, & Sun, 2015;Liu et al, 2016;Mei et al, 2014;Welliver et al, 2018). Although this treatment is therapeutic for a demyelinating disease, disrupting ACh signaling may be detrimental to oligodendroglia in other contexts.…”
mentioning
confidence: 99%
“…Further studies on modulated V‐ATPase activity and TLR4 signaling in the context of de‐ and remyelination in vivo will be important to conduct and therefore deserve increased attention. Of note, a couple of recent studies identified other promising signaling pathways promoting (re)myelination in rodent models such as activated by teriflunomide (Göttle et al, ), the histamine receptor 3 modulator GSK247246 (Chen et al, ), the dual inhibitor VP3.15 (Medina‐Rodriguez et al, ), muscarinic receptor antagonists (Welliver et al, ) and contactin‐2/TAG‐1 (Zoupi et al, ). Although, these are attractive targets they have not yet advanced in terms of clinical assessment and application.…”
Section: Discussionmentioning
confidence: 99%